Fermented and unfermented palm kernel cake as broiler chicken - P.P Ketaren; A.P Sinurat; D Zainuddin; T Purwadaria; I.P Kompiang (Jurnal Ilmu Ternak dan Veteriner, 1999)
feed. Two hundred and ten, day-old broiler chicks were used for this study. They were allotted to 6 different diets containing either BIS or FBIS at 3 different levels (5, 10 and 15%) and one control diet. The results showed that 5% BIS and 5% FBIS could be used in broiler diet without adversely affecting feed intake, weight gain and feed conversion ratio. FCR of those diets were significantly (P<0.05) better than the control diet. Carcass yields were not significantly affected by feeding of BIS nor FBIS. The FBIS diet produced less abdominal fat than the BIS diet.   Key words : Palm kernel cake, fermentation, broilers